2022
DOI: 10.3390/ani12162085
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Population Trends of Species with Imperfect Detection: Double Count Analyses and Simulations Confirm Reliable Estimates in Brown Frogs

Abstract: Most animal species are detected imperfectly and overlooking individuals can result in a biased inference of the abundance patterns and underlying processes. Several techniques can incorporate the imperfect detection process for a more accurate estimation of abundance, but most of them require repeated surveys, i.e., more sampling effort compared to single counts. In this study, we used the dependent double-observer approach to estimate the detection probability of the egg clutches of two brown frog species, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Therefore, clutches can be easily spotted and recognized and their number corresponds to the number of breeding females in a population in a given season. Detection probability analyses showed that the detection probability of clutches is >95%; therefore, clutch counts enable reliable estimates of population trends [24]. Preferred sites for egg-laying are perennial and slow-flowing waterbodies, where hatching typically occurs within 2 or 3 weeks and is followed by a relatively long tadpole stage which, depending on water conditions, lasts about 2-3 months [22].…”
Section: Study Area and Study Speciesmentioning
confidence: 99%
“…Therefore, clutches can be easily spotted and recognized and their number corresponds to the number of breeding females in a population in a given season. Detection probability analyses showed that the detection probability of clutches is >95%; therefore, clutch counts enable reliable estimates of population trends [24]. Preferred sites for egg-laying are perennial and slow-flowing waterbodies, where hatching typically occurs within 2 or 3 weeks and is followed by a relatively long tadpole stage which, depending on water conditions, lasts about 2-3 months [22].…”
Section: Study Area and Study Speciesmentioning
confidence: 99%
“…Therefore, clutches can be easily spotted and recognized and their number corresponds to the number of breeding females in a population in a given season. Detection probability analyses showed that the detection probability of clutches is >95%; therefore, clutch counts enable reliable estimates of population trends [24]. Preferred sites for egg-laying are perennial and slow-flowing waterbodies, where hatching typically occurs within 2 or 3 weeks and is followed by a relatively long tadpole stage which, depending on water conditions, lasts about 2-3 months [22].…”
Section: Study Area and Study Speciesmentioning
confidence: 99%
“…This allowed us to optimize time when more observers are available, without influencing detections. As we performed multiple clutch counts in the same year, we reported the highest count for each breeding site, which represents the minimum number of breeding females in each wetland [24]. In rare cases, we detected a few freshly laid egg clutches after the peak of the breeding season.…”
Section: Field Monitoring and Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, trends that rely on changes in relative abundance may be biased because they assume that detection probability remains constant. Additionally, simulations have suggested that accurately identifying population trends becomes difficult when detectability <80% ( Falaschi et al, 2022 ), such as for smaller, more cryptic species. Studies that directly estimate detection probability can greatly minimize this source of bias, resulting in more robust inferences about the population, and leading to more informed conservation actions.…”
Section: Introductionmentioning
confidence: 99%